PENGARUH PENERAPAN SISTEM MANAJEMEN KINERJA (SMK) TERHADAP PENCAPAIAN KINERJA PEGAWAI PERUM PERHUTANI DIVISI REGIONAL JAWA TENGAH - Yunitasari, Yunitasari; Haribowo, Putut (Politeknik Negeri Semarang, 2014)
The objective of this final report is to know influence of the implementation of performance management system (PMS) to employee’s performance at Perum Perhutani Divisi Regional Jawa Tengah. Observations, interviews, questionnaires, and literature studies are the instruments used to collect data. Questionnaires were distributed to 57 employees as respondents.The analysis data used the method of multiple linear regression coefficient analysis. Regression analysis is used to determine the influence of performance management system (PMS) to employees’ performance. Data are processed using SPSS 18.00.The data showed that the calculation of regression coefficients was Y = 0,285X1 + 0,285X2 + 0,371X3. It means that result of regression gives positive influence on employees’ performance. The coefficient of determination is 0.289. It means that the employees’ performance of 28,9% is influenced by performance management system (PMS). While the rest of 71,1% is influenced by other factors. The value of variable regression coefficient indicates a positive effect, Performance Management System (PMS) has significant influence to employees’ performance.The recommendation in this study are Perum Perhutani should improve evaluation performance, especially; supervisors identify problems and provide solutions. Implementation performance, especially; employees strive to achieve planned performance targets. Planning performance, especially; superiors and subordinates set performance targets that are relevant as well as employees know clearly how performance is measured.